Aortitis PET Imaging in VEXAS Syndrome: A Case Report. (7th February 2023) - Grambow-Velilla, Julia; Braun, Thorsten; Pop, Gabriel; Louzoun, Astrid; Soussan, Michael
Abstract: VEXAS (vacuoles, E1 enzyme, X-LINKED, autoinflammatory, somatic) syndrome is a complex inflammatory disease associated with somatic mutations of the ubiquitin-like modifier activating enzyme 1 ( UBA1 ) gene. A 75-year-old man with a medical history of thrombophlebitis, leukocytoclastic vasculitis, chronic inflammatory arthralgia, elevated inflammatory markers, and anemia was diagnosed with VEXAS syndrome. 18 F-FDG PET/CT showed thoracic aortitis, a rare involvement during VEXAS syndrome. Corticosteroid therapy monitored with 18 F-FDG PET/CT led to a complete metabolic response.